Earned Value Concept as a Method to Analyze Cost and Time Control - Budi Suryo Utomo; Kartono Wibowo; Soedarsono S (JACEE (Journal of Advanced Civil and Environmental Engineering), 2022)
The successful construction of infrastructure is dependent on many aspects, including at least time, cost, and control. With good control, deviations during the execution of work are expected to be minimized. In the case of the "MAS BIMACIKA" Service Office Building Construction project, acceleration of construction becomes an issue. Acceleration needs more resources than normal conditions, the addition of resources is required to achieve productivity value as planned. This study aimed to examine time and cost performance in the "MAS BIMACIKA" Service Office Building Construction Project. The Earned Value Concept, and the Crashing and Overlapping method used to analyze the costs resulting from the acceleration of work, were adopted in the process of controlling. Budget Cost of Work Schedule, Budget Cost of Work Performance, and Actual Cost of Work Performance were the parameters of the study. From the results of the analysis carried out until week 5, it is observed that the work could be completed earlier. This condition is indicated by the value of BCWP which is higher than BCWS. However, from the cost perspective, the construction resulted in wastage. This finding is confirmed by the value as shown in BCWP which is below ACWP. The analysis results until the 10th week show that the work could be completed earlier. This finding is indicated by the value of BCWP which is higher than BCWS. In terms of costs, the contractors still gained profit. This statement is supported by the value of ACWP which is below BCWP.